Rapid stromal remodeling by short‐term VEGFR2 inhibition increases chemotherapy delivery in esophagogastric adenocarcinoma. Issue 4 (3rd March 2020) - Steins, Anne; Klaassen, Remy; Jacobs, Igor; Schabel, Matthias C.; van Lier, Monique G. J. T. B.; Ebbing, Eva A.; Hectors, Stefanie J.; Tas, Sander W.; Maracle, Chrissta X.; Punt, Cornelis J. A.; Siebes, Maria; Bergman, Jacques J. G. H. M.; et al.
Abstract : Anti‐angiogenic agents combined with chemotherapy is an important strategy for the treatment of solid tumors. However, survival benefit is limited, urging the improvement of combination therapies. We aimed to clarify the effects of vascular endothelial growth factor receptor 2 (VEGFR2) targeting on hemodynamic function and penetration of drugs in esophagogastric adenocarcinoma (EAC). Patient‐derived xenograft (PDX) models of EAC were subjected to long‐term and short‐term treatment with anti‐VEGFR2 therapy followed by chemotherapy injection or multi‐agent dynamic contrast‐enhanced (DCE‐) MRI and vascular casting. Long‐term anti‐VEGFR2‐treated tumors showed a relatively lower flow and vessel density resulting in reduced chemotherapy uptake. On the contrary, short‐term VEGFR2 targeting resulted in relatively higher flow, rapid vasodilation, and improved chemotherapy delivery. Assessment of the extracellular matrix (ECM) revealed that short‐term anti‐angiogenic treatment drastically remodels the tumor stroma by inducing nitric oxide synthesis and hyaluronan degradation, thereby dilating the vasculature and improving intratumoral chemotherapy delivery. These previously unrecognized beneficial effects could not be maintained by long‐term VEGFR2 inhibition. As the identified mechanisms are targetable, they offer direct options to enhance the treatment efficacy of anti‐angiogenic therapy combined with chemotherapy in EAC patients. Abstract : Anti‐angiogenic therapies are combined with chemotherapy to treat cancers. Here, we reveal that therapy efficacy is greatly improved through previously unrecognized effects of VEGFR2 inhibition on tumor stroma in esophagogastric adenocarcinoma. Short‐term VEGFR2 inhibition results in activated fibroblasts that express FGF2 and hyaluronidase‐2, which enhances NO synthesis and hyaluronan degradation. This results in vasodilation, improved intratumoral perfusion, and chemotherapy delivery.